Stability and uniform ultimate boundedness of solutions of some third-order differential equations (2011)
The paper is concerned with the stability and uniform ultimate boundedness for all solutions of a third order nonlinear differential equations (1.1). Sufficient conditions under which all solutions x(t), its first and second derivatives tend to zero as t → ∞ are given.